The effect of ergometer design on rowing stroke mechanics - Greene, A. J.; Sinclair, P. J.; Dickson, M. H.; Colloud, F.; Smith, R. M. (Scandinavian Journal of Medicine & Science in Sports, 2013)
The effect of rowing ergometer design upon power delivery and coordination patterns of the rowing stroke was analyzed for 14 elite rowers. Rowers were tested in three ergometer conditions: the fixed stretcher Concept2c ergometer, the Concept2c ergometer mounted on sliding rails, and the sliding stretcher RowPerfect ergometer. Ergometers were instrumented to measure the external force generated at the handle and the foot stretcher and a nine-segment inverse dynamics model used to calculate joint and overall power delivery. Peak power generation and absorption at the knee joint was significantly greater, and total power delivered to the ergometer delayed on the fixed stretcher ergometer when compared to the sliding stretcher ergometers. No differences were found in the mechanical energy delivered to the handle of the three ergometers; however, greater joint mechanical energy production of the lower limb reduced mechanical efficiency when rowing the Concept2c fixed ergometer. The fixed foot stretcher on the Concept2c fixed ergometer acts to increase the inertial forces that the rower must overcome at the catch, increasing the moment and power output at the knee, and affecting the coordination pattern during the recovery phase.